Extracellular superoxide production by key microbes in the global ocean. (10th July 2019) - Sutherland, Kevin M.; Coe, Allison; Gast, Rebecca J.; Plummer, Sydney; Suffridge, Christopher P.; Diaz, Julia M.; Bowman, Jeff S.; Wankel, Scott D.; Hansel, Colleen M.
ABSTRACT: Bacteria and eukaryotes produce the reactive oxygen species superoxide both within and outside the cell. Although superoxide is typically associated with the detrimental and sometimes fatal effects of oxidative stress, it has also been shown to be involved in a range of essential biochemical processes, including cell signaling, growth, differentiation, and defense. Light‐independent extracellular superoxide production has been shown to be widespread among many marine heterotrophs and phytoplankton, but the extent to which this trait is relevant to marine microbial physiology and ecology throughout the global ocean is unknown. Here, we investigate the dark extracellular superoxide production of five groups of organisms that are geographically widespread and represent some of the most abundant organisms in the global ocean. These include Prochlorococcus, Synechococcus, Pelagibacter, Phaeocystis, and Geminigera . Cell‐normalized net extracellular superoxide production rates ranged seven orders of magnitude, from undetectable to 14, 830 amol cell −1 h −1, with the cyanobacterium Prochlorococcus being the lowest producer and the cryptophyte Geminigera being the most prolific producer. Extracellular superoxide production exhibited a strong inverse relationship with cell number, pointing to a potential role in cell signaling. We demonstrate that rapid, cell‐number–dependent changes in the net superoxide production rate by Synechococcus and Pelagibacter arose primarily from changes in gross production of extracellular superoxide, not decay. These results expand the relevance of dark extracellular superoxide production to key marine microbes of the global ocean, suggesting that superoxide production in marine waters is regulated by a diverse suite of marine organisms in both dark and sunlit waters.